Mechanical properties of trabeculae and osteocyte morphology change significantly in different areas of the necrotic femoral head - He, Min-Cong; Tian, Jia-Qing; He, Xiao-Ming; Yang, Peng; Lin, Tian-Ye; Zhang, Qing-Wen; He, Wei; Wei, Qiu-Shi (Frontiers in Cell and Developmental Biology, 2023)
Background: Osteonecrosis of the femoral head (ONFH) is a complex hip ailment. The precise changes in bone tissue during the disease's onset remain unclear. It is vital to assess both quantity and quality of trabecular state in a necrotic femoral head.To identify and contrast the ultrastructural changes in osteocyte morphology and nanomechanical characteristics within various regions of necrotic femoral heads.Between December 2016 and May 2023, we gathered ten necrotic femoral heads from patients and five femoral heads from cadavers. The samples from the necrotic femoral heads were categorized into three areas: necrotic, sclerotic, and normal. Our assessment methods encompassed HE staining, Sclerostin (SOST) immunohistochemistry, micro-computed tomography (CT), nanoindentation, and acid-etched scanning electron microscopy (SEM). These techniques enabled us to examine SOST expression, trabecular microstructure, micromechanical properties of trabeculae, and modifications in osteocyte morphology at the ultrastructural level.The protein level of SOST was found lower in sclerotic area. In necrotic area, decreased value of BV/TV, Tb.Th, and Tb.N and increased value of Tb.Sp were found while higher mean values of BT/TV, Tb.N, Tb.Th and lower Tb.Sp indicated that the structural characteristics of trabeculaes in sclerotic area were significantly changed. Compared with the healthy area, the elastic modulus and hardness in sclerotic area were significant higher than necrotic, normal and control while those in necrotic areas was significantly lower than that in healthy area. The number of osteocytes tended to increase in sclerotic area with more canalicular compared to healthy area and control group.These results imply that the stress distribution within the sclerotic area could potentially lead to enhanced trabecular quality and quantity. This effect is also reflected in the increased count of osteocytes and their canaliculars. It is plausible that sclerotic trabecular bone plays a pivotal role in the repair of necrotic femoral heads.